The Relationship Of Knowledge And Behavior About Nutrition To The Event Of Anemia In Adolescent Women In The Environment V Bamboo Field New Neighborhood - Dwi Ris Hasanah S; Helena Fransysca (Science Midwifery, 2020)
Nutrition or also called nutrition, is the study of food and its relationship to health. This study aims to determine the relationship of knowledge and behavior about nutrition to the incidence of anemia in adolescent girls. The research method used is pre-experimental with the design of "The One Shot Case Study". The population in this study amounted to 30 young women who are in Neighborhood V Village Baru Ladang Bambu. The sample in this study was 30 by total samplingThe results showed that the majority of respondents who had sufficient knowledge were 18 people (60%) the majority had active behavior as many as 18 people (60%) the majority had anemia as many as 12 people (40%) based on the chi-square statistical test obtained p value = 0.000. This means that the p value is smaller than the p value (0.05) and thus Ho is rejected and Ha is accepted, that is, knowledge and behavior about nutrition in adolescent girls have a significant relationship with the incidence of anemia. It is suggested to young women in Neighborhood V of Kelurahan Baru Ladang Bambu to meet the nutritional needs of the body and seek information about anemia.